Relationship between Nitrate and Phosphate with Phytoplankton Abudancein the Inundation of PLTA Koto Panjang Reservoir Batu Bersurat village, XIII Koto Kampar Districts, Kampar Regency, Riau Province - Dameyana S.C Lumban Tobing; Asmika Harnalin Simarmata; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbtractMany activities in the inundation of PLTA Koto Panjang Recervoir Batu Bersurat Village contributed organic matter that affect nitrate and phosphate concentration in water and increasing the abudance of phytoplankton. Aresearch aim to know the relationship between nitrate and phosphate with phytoplankton abudance in the inundation of PLTA Koto Panjang and it was conducted in June-July 2019. There were three sampling stations, namely Station I (tourisms and palm’s plantation), Station II (there were restaurant and trees around of station) and Station III (floating cage). In each station, there were three sampling points, in the surface (15 cm), in 2 Secchi depth (330 cm), and in 4 Secchi depth (660 cm). Sampling were conducted 4 times, once/week. Water quality parameter measured were nitrate, phosphate, phytoplankton abudance, transparency, temperature, pH, dissolved oxygen, free carbondioxide and BOD5 (Biochemical Oxygen Demand). The result shown: nitrate 0.06-0.08 mg/L, phosphate 0.05-0.09 mg/L, phytoplankton abundance 123,877-169,428 Cells/L, dissolved oxygen 6.35-6.88 mg/L, free carbondioxide 5-12.99 mg/L, temperature 29-31 oC, transparency 145.1-187.5 cm, pH 5-5.3 and biochemical oxygen demand (BOD5)4.03-8.90 mg/L. The relationship of nitrate and phosphate with phytoplankton abudance was very strong.Keywords:Kampar River, Floating Cage, Organic Matter, Water Quality, Mesotrophic